STRATEGI PEMBELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN KEAKTIFAN SISWA PADA MATERI PUISI DI KELAS XI SMA NEGERI 13 KOTA JAMBI - Vira Afiani; Agum Shohefi; Helty (Jurnal Lazuardi, 2026)
This study was motivated by the uneven student participation in Indonesian language learning on poetry material. Although the teacher had used strategies, media, and learning activities directed toward active learning, some students still tended to be passive when asked to ask questions, respond, or express their opinions. This study aimed to describe Indonesian language learning strategies in increasing student participation in poetry learning in grade XI at SMA Negeri 13 Kota Jambi. This research used a descriptive qualitative approach. The subjects consisted of one Indonesian language teacher and 20 grade XI students. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The results showed that the teacher implemented learning strategies through the delivery of learning objectives, the use of PowerPoint and video media, and the connection of poetry material with students’ experiences. However, student participation remained situational and had not developed evenly. Therefore, learning strategies need to be optimized through guiding questions, directed discussions, and reflective feedback to encourage more active student participation in learning.